EVALUASI KECUKUPAN BANGUNAN PADA AREA PERKANTORAN - Fajriati, Maulia; Rhomadhoni, Muslikha Nourma (Jurnal Kesehatan Masyarakat, 2024)
Fire is one of the impacts of potential hazards that often occur in the work area. Every company needs to have an automatic fire prevention and control system that meets fire prevention and control requirements, one of which is the administration of the placement of the number of workers that does not exceed the existing standard limits/rules. This type of research is a case study research that uses quantitative methods using secondary data, the data needed is data on the number of workers and building area in each work area. The results of the study show that the actual number of workers in each work area when compared to the number of people according to the standard, it can be said that they have met the standards that should be except for the 2nd floor of the Foundry office building. Researchers suggest companies to make improvements to all work area buildings to has an emergency response system that meets the requirements of integrated fire prevention and control and does not violate national and international standards.